Kebiasaan sarapan dan status gizi pelajar SMP - Makanoneng, Gwyneth Gwendellyn; Musa, Ester Candrawati; Sanggelorang, Yulianty (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: According to the Global Nutrition Report, rates of malnutrition among adolescents have declined, but cases of obesity and overweight have increased significantly. In 2019, an estimated 15.1% of adolescents were obese, while 5.7% were classified as underweight. This situation creates a nutritional problem known as the